ENHANCING STUDENTS’ COGNITIVE ABILITIES THROUGH STUDENTS-CENTERED LEARNING (SCL) - Faisal Amri; Nur Ekaningsih (Universitas Muhammadiyah Surakarta, 2017)
AbstractThis conceptual paper, presents about the result of discussion regarding students-centered learning improves students’ cognitive ability. SCL improves skills by developing cognitive ability lies within them as the first basic skill. It is important for students to have adequate cognitive abilities to keep up the materials which are being taught by teachers. Therefore, this paper will explain about cognitive ability. Cognitive ability which is affecting on learning process, has made some teachers struggle to seek a way how to improve it. There are few methods that have been chosen thoroughly for developing cognitive abilities on students. First is about developing thinking that refers mainly to how students think effectively and creatively. Second is about cooperative learning that refers to how students cooperate or work with other and effect of partners in learning process. Third is about learners’responsibility that has correlation with students’ responsible which affects on objectives of learning. Keywords: Students-Centered Learning, Cognitive Ability, Developing ThinkingSkill, Cooperative Learning, Learners’Responsibility.